2012
DOI: 10.1371/journal.pone.0045806
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/Akt Signaling Controls Mitochondrial Respiratory Capacity through 4E-BP1

Abstract: Akt, a serine/threonine kinase has been shown to stimulate glycolysis in cancer cells but its role in mitochondrial respiration is unknown. Using PTEN-knockout mouse embryonic fibroblasts (MEFPTEN−/−) with hyper-activated Akt as a cell model, we observed a higher respiratory capacity in MEFPTEN−/− compared to the wildtype (MEFWT). The respiratory phenotype observed in MEFPTEN−/− was reproduced in MEFWT by gene silencing of PTEN which substantiated its role in regulating mitochondrial function. The increased ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 49 publications
6
62
1
Order By: Relevance
“…Not much is known about PI3K/AKT pathway and its role in mitochondrial respiratory function in CLL cells; however, hyper-activation of AKT leading to increased mitochondrial respiration and thereby ATP synthesis by the 4E-BP1–mediated protein translation pathway has been reported (46). Inhibition of this mitochondrial respiration by the above-mentioned target-specific drugs further supports the notion that mitochondrial respiration is regulated by AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Not much is known about PI3K/AKT pathway and its role in mitochondrial respiratory function in CLL cells; however, hyper-activation of AKT leading to increased mitochondrial respiration and thereby ATP synthesis by the 4E-BP1–mediated protein translation pathway has been reported (46). Inhibition of this mitochondrial respiration by the above-mentioned target-specific drugs further supports the notion that mitochondrial respiration is regulated by AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways not explored here could also be involved. Recently, it was shown that mTORC1 and Akt increase mitochondrial volume and activity through translational regulation (63,64). Given that Akt activation consistently decreased mitochondrial function and FAO, we focused on transcriptional mechanisms in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Akt directly phosphorylates both pro-and antiapoptotic mitochondrial proteins such as Bcl-2-associated death protein (Bad) and the inhibitor of apoptosis proteins (XIAPs) to inhibit mitochondrial apoptosis [89]. Akt has also been shown to drive mitochondrial respiration through mTORC1-induced protein translation of respiratory complexes [92] and via mTORC2/Akt signalling in mitochondriallyassociated endoplamic reticulum membranes (MAMs) regulating growth, mitochondrial function and metabolism [93].…”
Section: Pink1 Function Overviewmentioning
confidence: 99%